Optimalisasi Kesejahteraan Masyarakat Desa Sumbung pada Era Covid-19 - Herwin Pisestiyani; Sandra Dewi Hartanti; Rama Adi Rianto; Nur Indah Andini; Fajar Agus Pradana; Anisa Rahmawati Seolikah; Qomsatun Istiqomah; Annisa Nur Hapsari; Haidar Muhammad Yasin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
The public's disobedience to the government's appeal shows that there is still a lack of education regarding the impact and dangers of COVID-19 as well as prevention facilities for COVID-19 which are still not fully accepted by the community. The objectives of carrying out the KKN-T activities in Sumbung Village during the COVID-19 pandemic include building the potential of the tourist area of Sumbung Village as an effort to increase regional income, prevent the spread of COVID-19 through socializing the application of clean and healthy lifestyles, and building people's thinking patterns to implement a healthy and clean lifestyle. The KKN-T IPB program activities in Sumbung Village, Cepogo District, Boyolali Regency were carried out from July 1 to August 26, 2020. The program carried out by the Sumbung Village KKN-T team included installing plastic droplet protectors or screen guards for shops or stalls, making infographic posters on healthy living habits in the new normal era, how to wash hands properly and distributing hand washing soap to madrasah students, as well as installing map boards for the tourism potential of Sumbung Village. Keywords: COVID-19, KKN-T, behaviour, Sumbung, sreen guard